Political Marketing Communication Strategy to be Elected as a Member of The Indonesia’s Parliament - Khairatun Niswa Aceh; Nur Kholisoh (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The involvement of women in efforts to meet the minimum representation quota of 30% in the legislature is not easy. An appropriate strategy is needed to win seats in the legislature, including implementing a political marketing communication strategy. Political marketing is commonly used in economic or entrepreneurial concepts for political elements. This study aims to determine Hetifah Sjaifudian’s Political Marketing Communication Strategy to be elected as a member of the Republic of Indonesia Parliament for 2019-2024. The research paradigm is constructivist with a qualitative approach and a case study research method. This study uses the political marketing communication theory put forward by Lees-Marshment. In a Product Oriented Party (POP), the leader carries out political planning activities and expects support from members and the public. The Sales Oriented Party (SOP) approach focuses on the communication strategy adopted by a party in persuading voters and the public to choose and want things offered by that party. The Market Oriented Party (MOP) approach focuses on public priorities collected from various data collection methods such as surveys, focus group discussions, consultations, meetings, interviews, gatherings, and internal discussions. The results of the research show that of the nine stages, the market research, communication, and campaign stages were important stages in winning Hetifah Sjaifudian.